Development of Library Management System using Web-Based Approach - Yip Lik Zeh; Noryusliza binti Abdullah (Applied Information Technology And Computer Science, 2023)
A Library management system is a software that is used to manage and run a library. It is important to help the library deliver its core services to the library user. The core services include showing the availability of  books in the library, managing the book inventory records, issuing the borrowing record, and issuing punishment to overdue borrow records systematically. However, the library in Sekolah Kebangsaan (Perempuan) Bandar Kluang (INTEG) (SKPBK) is using a manual system to run its library. It is appointing librarians to manage the book inventory records, borrowing records, and issue penalties on overdue borrow records manually. Therefore, a new web-based library management system is needed to replace the current manual system. The proposed system will be applied in the library of the SKPBK. By using this system, the library of SKPBK can be more efficient in doing its daily operations.